The physical properties and ion release of CPP‐ACP‐modified calcium silicate‐based cements. (December 2015) - Dawood, AE; Manton, DJ; Parashos, P; Wong, RHK; Palamara, JEA; Stanton, DP; Reynolds, EC
Abstract: Background: This study investigated the physical properties and ion release of casein phosphopeptide‐amorphous calcium phosphate (CPP‐ACP)‐modified calcium silicate‐based cements (CSCs) and compared the properties of a trial mineral trioxide aggregate (MTA) with two commercially available CSCs, Biodentine ™ and Angelus ® MTA. Methods: The setting time, solubility, compressive strength and Vickers surface microhardness of the three CSCs incorporated with 0%, 0.5%, 1.0%, 2.0% and 3.0% (w/w) CPP‐ACP were investigated. Release of calcium (Ca 2+ ), phosphate ions (P i ) and pH of the test cements were measured after 24, 72, 168 and 336 h of storage. Results: The addition of up to 1.0% CPP‐ACP into Biodentine ™ and 0.5% into the other cements did not adversely affect their physical properties except for the setting time. The addition of 0.5% CPP‐ACP increased Ca 2+ released from Biodentine ™ (after 168 and 336 h), Angelus ® MTA (after 168 h) and the trial MTA (after 72 h). The addition of 1.0–3.0% CPP‐ACP increased Ca 2+ and P i released from all the cements. Biodentine ™ released more Ca 2+ particularly in the early stages and showed shorter setting time and higher mechanical properties than the other cements. The mechanical properties of Angelus ® MTA and the trial MTA were similar. All the cements produced highly alkaline storage solutions. Conclusions: Up to 1.0% CPP‐ACP in Biodentine ™ improves Ca 2+ and P i release and 0.5% CPP‐ACP in Angelus ® MTA and the trial MTA improves Ca 2+ release without altering the mechanical properties and solubility. The addition of CPP‐ACP into CSCs prolonged the setting time.